Energy Efficiency Analysis of Network Slicing Algorithm on WiFI Network - Dimas Prakoso; Hilal Hudan Nuha; Rio Guntur Utomo (School of Computing, Telkom University, 2022)
The 5G network generation is a modern innovation after it was first introduced by the New Generation Mobile Network (NGMN). The rapid development of mobile devices is marked by the number of companies launching mobile devices with the latest network connection technology, namely the 5G network. In addition, the rapid development of technology has led to an increase in the number of network requirements that are increasingly current. The development of network virtualization and software network functions is proposed as Network Slicing technology. Network Slicing can integrate and distribute independent network resources so that users get services with low latency and high-reliability requirements. The Network Slicing algorithm can reduce energy wastage when used and aims to divide and allocate network resources into several parts in proportion to the expected resource ratio or priority.